Enhanced PLL-less grid synchronization algorithm amidst unbalanced and distorted three-phase grid conditions. (June 2023) - Kumar, Manish; Jarial, Raj Kumar; Verma, Anant Kumar; Nath, Ravindra; Torres, Miguel; González-Castaño, Catalina; Roncero-Sánchez, Pedro
Abstract: Fast and precise tracking of grid voltage attributes is essential for the smooth and reliable control and operation of grid-side converters. The synchronous reference-frame phase-locked loop (SRF-PLL) approach is commonly used for this purpose, although it has issues related to the stability limit and sluggish transient response. Consequently, PLL-less grid synchronization approaches are becoming increasingly prevalent. In this context, in the present paper, a discrete Fourier transform-based band pass filter (DFT-BPF) is designed in the prefiltering stage for the purpose of extracting the fundamental frequency positive sequence component (FFPS) from unbalanced and distorted grid conditions. Despite being widely used, the SRF-PLL is struggling with stability issues and demands tedious tuning effort. For this objective, a simple frequency estimator has been developed, which is capable of accurately estimating the fundamental frequency. Additionally, a curve fitting based error correction technique is employed to adaptively estimate the amplitude and phase-angle of the fundamental component without using frequency feedback loop. The experimental results validate the efficacy of the proposed scheme. Highlights: Quick non-adaptive pre-filter-based PLL-less grid synchronization scheme Rapid extraction of FFPS; and elimination of FFNS, DC-offset, and harmonics Reduced efforts in generating filtered orthogonal signals Better frequency tracking is possible with an open-loop frequency detection approach Error-free estimation of grid voltage amplitude/phase information is possible